LIFE IN IDIOMS: UNVEILING THE PHRASEOLOGICAL UNITS THAT CAPTURE THE ESSENCE OF LIVING (International journal of artificial intelligence, 2025)
Idioms are more than just colorful expressions; they are linguistic snapshots that encapsulate cultural wisdom, historical nuances, and the very essence of human experience. These phraseological units, which cannot be understood by simply adding up the meanings of their individual words, offer a unique window into how different societies perceive the world. From the mundane to the profound, idioms permeate our daily conversations, adding depth, humor, and a touch of local flavor.